Desenvolvimento de uma arquitetura de distribuição de realidade virtual e aumentada aplicada em ambientes educacionais - Nogueira, Keila de Fátima Chagas (2010)
Currently, access to information is increasingly easy because of the advancement of Information and Communication Technology (TIC), reflecting the popularization of computers and the Internet, both in schools as at home. In the same context research projects are being developed toward new teaching methodologies. These projects facilitate new educational methods compared with traditional methods. Today is possible to simulate several laboratories (physics, chemistry, mathematics) by a single computer lab. There are several technologies that support the creation of these systems, included Virtual Reality that lets you create Virtual models and environments and simulate them as if they were real. Another technology is Augmented Reality, where you can insert elements of virtual learning in real environments, which increases the number of alternative educational tools. However distributed systems Virtual Reality and Augmented Reality developed today are limited in the amount of virtual objects belonging to the environment used, another issue is that these systems use either Virtual or Augmented Reality to solve their problems independently, not completing the two technologies. Thus, this dissertation came with the proposal to develop a distribution architecture for Virtual and Augmented Reality, where any model or virtual environment may be distributed, which allows greater flexibility of the proposed architecture